Taphofacies analysis of the Middle Devonian Passagem Member (Cabeças Formation), Parnaíba Basin, Piauí, Brazil - Ponciano, L. (2010)
Taphonomic attributes of brachiopod-dominated macroinvertebrate assemblages from the Cabeças Formation (Givetian - late Famennian) are described in the present study. The shelly fossils are restricted to the unit?s lowest part, the Passagem Member (of Givetian age). The member is only recognized on the eastern border of the Parnaíba Basin, Brazil, and consists mostly of sigmoidal clinoforms (sandstones with asymptotic cross-stratification and climbing ripples) and interbedded hummocky cross-stratified tabular sandstone lobes. Three taphofacies have been identified and characterized in outcrops near the villages of Pimenteiras (Oiti) and Picos (Br-316, km 305), State of Piauí, on the basis of qualitative and quantitative analyses of the taphonomic signatures of macroinvertebrates and plant cuticles. Their origin is related to shallow-water turbidity currents (hyperpycnal flows) originated by a flooddominated fluvio-deltaic system entering shallow marine settings. The taphonomic attributes of taphofacies 1 indicate a proximal paleoenvironment, interpreted as the distal mouth-bar deposits of a flood-dominated fluvio-deltaic system. This taphofacies features the dominance of the brachiopod Pleurochonetes comstocki (Rathbun) (particularly in sandstones with asymptotic cross-stratification and climbing ripples), and results from the deceleration of highdensity turbidity currents, in which the unidirectional component of the hyperpycnal flow prevails. Basinward, the deposition of taphofacies 2 is related to the deceleration of low-density turbidity currents (in which the oscillatory component of the hyperpycnal flow prevails), characterizing tabular delta-front lobes with HCS, rich in terebratulid brachiopods. Lastly, taphofacies 3 has been originated by the upper part of the turbidity currents, charged with finegrained sediments, plant debris and mica flakes, deposited as laterally extensive silt/sand couplets at the end of the hyperpycnal flow. The integrated analysis of the taphofacies and composition of fossil assemblages corroborates the interpretation of the Passagem Member as the distal mouth-bar deposits and delta-front sandstone lobes of a flooddominated fluvio-deltaic system, as previously concluded by sedimentological studies.